Phenotypic profile of expanded NK cells in chronic lymphoproliferative disorders: a surrogate marker for NK-cell clonality - Bárcena, Paloma; Jara-Acevedo, María; Tabernero, María Dolores; López, Antonio; Sánchez, María Luz; García-Montero, Andrés C.; Muñoz-García, Noemí; Vidriales, María Belén; Paiva, Artur; Lecrevisse, Quentin; Lima, Margarida; Langerak, Anton W.; et al. (Oncotarget, 2015)
Currently, the lack of a universal and specific marker of clonality hampers the diagnosis and classification of chronic expansions of natural killer (NK) cells. Here we investigated the utility of flow cytometric detection of aberrant/altered NK-cell phenotypes as a surrogate marker for clonality, in the diagnostic work-up of chronic lymphoproliferative disorders of NK cells (CLPD-NK). For this purpose, a large panel of markers was evaluated by multiparametric flow cytometry on peripheral blood (PB) CD56(low) NK cells from 60 patients, including 23 subjects with predefined clonal (n = 9) and polyclonal (n = 14) CD56(low) NK-cell expansions, and 37 with CLPD-NK of undetermined clonality; also, PB samples from 10 healthy adults were included. Clonality was established using the human androgen receptor (HUMARA) assay. Clonal NK cells were found to show decreased expression of CD7, CD11b and CD38, and higher CD2, CD94 and HLADR levels vs. normal NK cells, together with a restricted repertoire of expression of the CD158a, CD158b and CD161 killer-associated receptors. In turn, NK cells from both clonal and polyclonal CLPD-NK showed similar/overlapping phenotypic profiles, except for high and more homogeneous expression of CD94 and HLADR, which was restricted to clonal CLPD-NK. We conclude that the CD94(hi)/HLADR+ phenotypic profile proved to be a useful surrogate marker for NK-cell clonality.